Wilhelm von Humboldt Bapak Pendidikan Sejarah - Purwanta, Hieronymus; Leo Agung Sutimin; Bramastia; Winarno; Endrise Septina Rawanoko; Deni Zein Tarsidi; Andrea Salsalova (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to trace the origins of history education. The research question raised is: How did history emerge as a school subject? This question intrinsically also raises other related questions, such as when, where, and who the figures were who gave birth to history as a school subject. This research is a literature review using historical methods. The source collection was conducted by copying and downloading digitally available sources, including both primary and secondary sources. The results indicate that history first became a school subject in the early 19th century in Prussia (present-day Germany). The figure who initiated and implemented the policy was Wilhelm von Humboldt, who at the time was an official at the Ministry of the Interior. History education was given the responsibility to use knowledge of the past as a medium for the formation of the whole person (Bildung). This responsibility makes history education more a part of the historical culture that developed in society, rather than a subordinate to the science of history, tasked with reconstructing past events.